Systemic Lupus Erythematosus (SLE) & Lupus Nephritis (LN) in Male: Presentation, Outcome & Poor Prognostic Factors - Kumar, Dileep; Gulzar, Kashif; Alawi, Fakhriya J; Najad, Sima; Ahmed, Maseer; Bibi, Aisha; Khan, Faraz; Elbadaw, Faisal; Al Hadari, Amna (British Journal of Healthcare and Medical Research, 2025)
Introduction: Systemic lupus erythematosus (SLE) is common in female, while lupus nephritis (LN) is more common in male. Methods: we analyze clinical & lab parameters of male SLE patients since 2009, also reported incidence, histopathological classes & outcome of LN. Results: Total 61 male patients were diagnosed with SLE. Antinuclear antibody (ANA), Ant Ds DNA antibody (ds DNA Ab) & Lupus anticoagulant (LA) were positive in 75.40%, 67.21% & 40.98% of patients respectively, also Low C3 & C4 were observed in 57.09% & 34.70% respectively. Incidence of LN was 54.09%. Constitutional manifestations were most common presenting complain in both LN & rest of the SLE patients (RoSLE) (LN vs RoSLE: 48.48% vs 57.14% p-value: >0.05). Regarding lab parameters, RoSLE patients show more positive ANA (LN vs RoSLE: 69.69% vs 82.14%, p=>0.05), ds DNA Ab (LN vs RoSLE: 60.60% vs 75%, p=>0.05) & LA (LN vs RoSLE: 33.33% vs 50%, p=>0.05) titer. Mean creatinine (Cr) was 0.90±0.70 mg/dl in LN & 0.81±0.23 (p=>0.05) in the RoSLE patients. also decrease serum Albumin (Alb) was observed in LN patients (LN vs RoSLE: 2.85±1.85 vs 4.25±0.82, p=<0.05). Class IV was most common lesion in 48.48%, also 24.24% LN patients reached to chronic kidney disease stage V. CKD V-LN patients were older (CKD vs CKD-V: 37.68±12.18 vs 43±10.75, p=<0.05) & have positive ANA (37.5%), ds DNA ab (37.5%) & LA (25%) titer, also low C3 were more common in CKD-V patients than low C4 [CKD other stages vs CKD-V: (Low C3; 44% vs 62.5%, p>0.05) & (Low C4; 32% vs 25%, p>0.05). Median Cr & Alb was 0.9(0.52) & 2.6(1.7) in other stages of CKD, while 2.8(4.9) & 3.17(1.27) in CKD-V patients. Mean duration from diagnosis of LN to attend CKD-V was 13.34±7.50 years. Conclusion: More than half of SLE patients had LN, with class IV is most common histopathological lesion. Incidence of CKD-V in LN was significantly high, belongs to older age group and have minimal extra-renal manifestations, that probably explains late presentation & relatively poor renal outcome, however there was no statistical significant risk factor between LN & the RoSLE.